Oblique nonvolcanic seafloor spreading in Lena Trough, Arctic Ocean - Snow, Jonathan E.; Hellebrand, Eric; Von Der Handt, Anette; Nauret, Francois; Gao, Yongjun; Schenke, Hans Werner (Geochemistry, Geophysics, Geosystems, 2011)
Passive rifting and the early non-volcanic formation of ocean basins are fundamental aspects of the plate tectonic cycle. Cenozoic plate margins where this has occurred are rare. Here we present new observations from Lena Trough in the Arctic Ocean that bear on the early phase of oceanic spreading in such rifts. Lena Trough is an oblique seafloor rift system bounding the North American and Eurasian plates, and connecting neighboring Gakkel Ridge with the rest of the global mid-ocean ridge system. Mapping and sampling show widespread mantle outcrop along two parallel basement ridges bounded by steeply dipping normal faults. Volcanism is limited to the intersection with Gakkel Ridge and to minor eruption of strongly potassic alkali basalts in a single location. Non-eruptive magmatism is shown by an increase in plagioclase-and vein-bearing lithologies over residual peridotite in the center of Lena Trough. Normal mid-ocean ridge stairstep geometry and obvious low-angle detachments as seen at other ridges are absent. Lena Trough thus is an example of a young nonvolcanic continental rift that is just now beginning the transition to oblique nonvolcanic seafloor spreading. This style of oblique rifting, without the formation of striated large-scale low-angle detachments appears to be a major mode of crust formation on ultraslow spreading ridges. The sharp transition from the continental margins on either side to nonvolcanic rifting, with mantle slab exhumation in the rift may provide a model for the early evolution of oblique continental rifts, such as the Cote d'Ivoire/NE Brazil conjugate margins. Copyright 2011 by the American Geophysical Union.